(untitled) (El-Wahat Journal for Research and Studies, 2025)
Although Algeria Has Many Cultural Heritage Sites, It Can Make It A Tourist Destination With Distinction For A Wide Range Of Tourists. However, There Is Limited Number Of Local Tourists Flocking To These Sites. This Study Aimed To Examine The Factors Affecting Tourists’ Intentions To Visit Cultural Heritage Sites; And To This End A Convenience Sample Of 126 Domestic Tourists In Algeria Was Relied Upon. Multiple Linear Regression Has Been Used To Test The Study’s Hypotheses. The Results Revealed That The Behavioral Intention To Visit Cultural Heritage Sites Is Affected By Tourists’ Attitudes; Electronic Word Of Mouth; Perception Of Cost Fairness; And Quality Of Tourist Service, Also Indicated That The Perceived Risk Has No Significant Effect On Local Tourists’ Intentions. In The End, We Will Provides Some Recommendations To Various Stakeholders Involved In Marketing Cultural Heritage Sites To Improve Their Ability To Attract More Local And International Tourists. Keywords: Cultural Heritage Marketing, Cultural Cities, Electronic Word Of Mouth, Tourists, Algeria.